Group Delay measurements of ultrabroadband pulses generated in highly nonlinear fibers - Szczepanek, Jan; Kardaś, Tomasz M.; Stepanenko, Yuriy (Photonics Letters of Poland, 2016)
Ultra broadband supercontinuum pulses are commonly used as a source of different wavelengths from a wide spectral bandwidth or as a source of very short pulses. However the processes responsible for wide spectral broadening are still under investigation. In this paper we examine the temporal and spectral characteristics of the pulses broadened upon propagation in the highly nonlinear photonics crystal fibers with different dispersion profiles. Generated supercontinuum pulses were experimentally characterized using cross-correlation frequency resolved optical gating technique. Full Text: PDF References M. Bradler, P. Baum, and E. Riedle, "Femtosecond continuum generation in bulk laser host materials with sub-?J pump pulses", Appl. Phys. B 97, 561 (2009). CrossRef T. M. Kardaś, B. Ratajska-Gadomska, W. Gadomski, A. Lapini, and R. Righini, "The role of stimulated Raman scattering in supercontinuum generation in bulk diamond", Opt. Express 21, 24201 (2013). CrossRef A. Brodeur and S. L. Chin, "Band-Gap Dependence of the Ultrafast White-Light Continuum", Phys. Rev. Lett. 80, 4406 (1998). CrossRef R. R. Alfano, ed., The Supercontinuum Laser Source: Fundamentals with Updated References, 2nd ed (Springer, 2006). DirectLink A. L. Gaeta, Phys. "Catastrophic Collapse of Ultrashort Pulses", Rev. Lett. 84, 3582 (2000). CrossRef J. M. Dudley, G. Genty, and S. Coen, "Supercontinuum generation in photonic crystal fiber", Rev. Mod. Phys. 78, 1135 (2006). CrossRef M. Klimczak, B. Siwicki, P. Skibiński, D. Pysz, R. Stępień, A. Heidt, C. Radzewicz, and R. Buczyński, "Coherent supercontinuum generation up to 2.3 ?m in all-solid soft-glass photonic crystal fibers with flat all-normal dispersion", Opt. Express 22, 18824 (2014). CrossRef D. J. Kane and R. Trebino, "Characterization of arbitrary femtosecond pulses using frequency-resolved optical gating", IEEE J. Quantum Electron. 29, 571 (1993). CrossRef J. Dudley, X. Gu, L. Xu, M. Kimmel, E. Zeek, P. O'Shea, R. Trebino, S. Coen, and R. Windeler, "Cross-correlation frequency resolved optical gating analysis of broadband continuum generation in photonic crystal fiber: simulations and experiments", Opt. Express 10, 1215 (2002). CrossRef N. Nishizawa and T. Goto, "Experimental analysis of ultrashort pulse propagation in optical fibers around zero-dispersion region using cross-correlation frequency resolved optical gating", Opt. Express 8, 328 (2001). CrossRef X. Gu, L. Xu, M. Kimmel, E. Zeek, P. O'Shea, A. P. Shreenath, R. Trebino, and R. S. Windeler, "Frequency-resolved optical gating and single-shot spectral measurements reveal fine structure in microstructure-fiber continuum", Opt. Lett. 27, 1174 (2002). CrossRef S. Roy, S. K. Bhadra, and G. P. Agrawal, "Effects of higher-order dispersion on resonant dispersive waves emitted by solitons", Opt. Lett. 34, 2072?2074 (2009). CrossRef S. Bose, S. Roy, R. Chattopadhyay, M. Pal, and S. K. Bhadra, "Experimental and theoretical study of red-shifted solitonic resonant radiation in photonic crystal fibers and generation of radiation seeded Raman soliton", J. Opt. 17, 105506 (2015). CrossRef T. Roger, M. F. Saleh, S. Roy, F. Biancalana, C. Li, and D. Faccio, "High-energy, shock-front-assisted resonant radiation in the normal dispersion regime", Phys. Rev. A 88, (2013). CrossRef G. P. Agrawal, Nonlinear Fiber Optics, Fifth edition (Elsevier/Academic Press, 2013). DirectLink J. Szczepanek, T. Kardaś, M. Nejbauer, C. Radzewicz, and Y. Stepanenko, "Simple all-PM-fiber laser system seeded by an all-normal-dispersion oscillator mode-locked with a nonlinear optical loop mirror", Proc. SPIE 9728, 972827 (2016). CrossRef C. Iaconis and I. A. Walmsley, "Self-referencing spectral interferometry for measuring ultrashort optical pulses", IEEE J. Quantum Electron. 35, 501 (1999). CrossRef L. E. Hooper, P. J. Mosley, A. C. Muir, W. J. Wadsworth, and J. C. Knight, "Coherent supercontinuum generation in photonic crystal fiber with all-normal group velocity dispersion", Opt. Express 19, 4902 (2011). CrossRef J. Szczepanek, T. M. Kardas, and Y. Stepanenko, "Sub-160-fs pulses dechriped to its Fourier transform limit generated from the all-normal dispersion fiber oscillator", Optical Society of America Frontiers in Optics conference, FTu3C?2 (2016). CrossRef G. Genty, M. Lehtonen, and H. Ludvigsen, "Effect of cross-phase modulation on supercontinuum generated in microstructured fibers with sub-30 fs pulses", Opt. Express 12, 4614 (2004). CrossRef S. Roy, S. K. Bhadra, K. Saitoh, M. Koshiba, and G. P. Agrawal, "Dynamics of Raman soliton during supercontinuum generation near the zero-dispersion wavelength of optical fibers", Opt. Express 19, 10443 (2011). CrossRef Y. Liu, Y. Zhao, J. Lyngso, S. You, W. L. Wilson, H. Tu, and S. A. Boppart, "Suppressing Short-Term Polarization Noise and Related Spectral Decoherence in All-Normal Dispersion Fiber Supercontinuum Generation", J. Light. Technol. 33, 1814 (2015). CrossRef